2011
DOI: 10.1007/s11207-011-9734-5
|View full text |Cite
|
Sign up to set email alerts
|

Supergiant Complexes of Solar Activity and Convection Zone

Abstract: The global distribution of solar surface activity (active regions) is apparently connected with processes in the convection zone. The large-scale magnetic structures above the tachocline could in a pronounced way be observable in the surface magnetic field. To get the information regarding large-scale magnetic formations in the convection zone, a set of solar synoptic charts (Mount Wilson 1998-2004.02 nm) have been analyzed. It is shown that the longitudinal dimensions and dynamics of supergiant complexes of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…, which is similar to that used in our previous solar studies (Arkhypov et al 2011(Arkhypov et al , 2013. Figure 7 shows the values of τ 1 and τ 2 obtained with the old (Arkhypov et al 2015a) and current (modified) methods.…”
Section: Modified Methods For Harmonics' Timescale Measurementsupporting
confidence: 66%
See 1 more Smart Citation
“…, which is similar to that used in our previous solar studies (Arkhypov et al 2011(Arkhypov et al , 2013. Figure 7 shows the values of τ 1 and τ 2 obtained with the old (Arkhypov et al 2015a) and current (modified) methods.…”
Section: Modified Methods For Harmonics' Timescale Measurementsupporting
confidence: 66%
“…It has been found that the large-scale pattern of solar activity shows the timescales of large longitudinal harmonics (with numbers m < 20), in agreement with Kolmogorov's theory of turbulence (Arkhypov et al 2011(Arkhypov et al , 2013. Moreover, turbulent cascades have now been identified in the power spectra of solar activity variations at scales up to 380 Mm, or at m  10 (Arkhypov et al 2013).…”
Section: Introductionsupporting
confidence: 69%
“…Breaking up the light curve in chunks of one rotation period length and calculation of individual C The study of the longitudinal distribution of stellar activity helps to reveal photospheric manifestations of deep convection. These manifestations were found in the Sun (Arkhypov et al 2011(Arkhypov et al , 2013 and reproduced in numerical modeling (Weber et al 2013). 4.…”
Section: Satisfied Then We Replace the Measured F(t) With The Value mentioning
confidence: 71%
“…However, turbulent cascades have now been identified in the power spectra of variations of solar activity at scales up to 380 Mm (Arkhypov et al 2013). Moreover, the timescales of variability for activity complexes of global sizes (>190 Mm) were shown to be consistent with the predictions of Kolmogorov's theory of turbulence (Arkhypov et al 2011(Arkhypov et al , 2013. These features are the "fingerprints" of turbulence deep in the solar CZ.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation